Passive surveillance of STI pathogens in Cape Town, South Africa: A six-month molecular epidemiology study - Moodley, Clinton (Department of Public Health and Family Medicine, 2024)
Background: Sexually transmitted infections are among the most commonly occurring globally, with countries in sub-Saharan Africa exhibiting disproportionately higher prevalence rates. Reports indicate the need for accurate detection, epidemiological characterisation, and appropriate management of these infections. This prospective passive surveillance study sought to document local STI prevalence and to evaluate the potential of a molecular assay as a surveillance tool in our setting. Methods: Urogenital swabs, submitted to Groote Schuur Hospital over a period of 6 months, for routine microbiological investigations, were subjected to a commercial multiplex PCR assay to determine the distribution of STI pathogens. Correlations between detected organisms and clinical and demographic information were determined using Stata® software. Results: A total of 148 urogenital swabs were collected and tested, with the majority from women. Up to 83.79% of the samples tested positive for one or more pathogen, with all seven assayed pathogens detected in one or more sample. Ureaplasma parvum was the most prevalent pathogen detected overall, with a 6-month period prevalence of 42.57%, followed by N. gonorrhoeae (37.84%), M. hominis (34.46%), U. urealyticum (23.65%), T. vaginalis (11.49%), C. trachomatis (10.14%), with M. genitalium (1.35%) the least prevalent. There were several different combinations of co-infections with multiple pathogens, with one sample testing positive for five organisms. M. hominis and T. vaginalis were only detected in co-infection with other pathogens. Persons aged 17-30- and 31-40- years old were 51-times and 16-times, respectively, more likely to test PCR-positive for one or more STI pathogen. Samples submitted with non-urogenital specific indications were 11.82 times more likely to test positive for C. trachomatis. There was an association between samples submitted for GBS screening and PCR-positivity for any of the pathogens tested, which were 3.03 times more likely to test positive for U. parvum. Routine microbiological investigations only detected three infections. Conclusions: There is a significantly higher than expected rate and difference in organism distribution of STI prevalence in Cape Town, South Africa as compared with global and regional estimates. The use of molecular testing methods may improve detection, providing rapid results, which may allow for tailored guidelines and interventions to limit spread and resistance.